Logopedska obravnava bolnikov s Parkinsonovo boleznijo - Ogrin, Maja (Medicinski razgledi, 2000)
Parkinson's disease is a degenerative neurological disease progressing by affecting the abilities of communication (verbal, non-verbal, written). These disorders are present in a half to three-fourths of patients. Parkinson's disease is frequently accompanied by disorders of swallowing, observed in about 50% of patients. It is often combined with numerous other disorders suchas: difficult reading, memorizing problems, rapid fatigue; disturbed motoractivity of the dominant hand, and similar, all of which puts further strain on the already difficult communication and swallowing. The basic goal of logapedic treatment is to maintain and activate the affected abilities, therewith moderating the social isolation of these patients. At the Institute for Rehabilitation in Ljubljana the logopedic treatment of Parkinsonian patients makes part of the programs of complex rehabilitation (physiotherapy, occupational therapy, psychological and social treatment etc.). The speech therapist coordinates his work with other members of the team and collaborateswith the patient's family
Keywords: Parkinson disease; Parkinsonova bolezen; sporazumevanje; Therapy; motnje; Diagnosis; logopedija; Speech therapy; Communicative disorders; Dysarthria; Deglutition disorders; Voice disorders